Radiographic Risk Factors Associated With Adverse Local Tissue Reaction in Head-Neck Taper Corrosion of Primary Metal-on-Polyethylene Total Hip Arthroplasty. Issue 8 (15th April 2021) - Kwon, Young-Min; An, Shuai; Yeo, Ingwon; Tirumala, Venkatsaiakhil; Chen, Wenhao; Klemt, Christian
Abstract : Background: Adverse local tissue reactions (ALTRs) in metal-on-polyethylene (MoP) total hip arthroplasty (THA) with head-neck taper corrosion are multifactorial, involving implant and patient factors. This study aimed to identify any potential clinical risk factors associated with failed MoP THA due to head-neck taper corrosion. Methods: A series of 146 MoP THA patients was investigated: (1) ALTR (n = 42) on metal artifact sequence MRI and (2) non-ALTR (n = 104). Both cohorts were compared regarding femoral neck shaft angle, acetabular implant orientation, component size, femoral head offset, measurement of medial and vertical femoral offsets, and femoral stem alloy. Results: The occurrence of ALTR was associated with increased radiographic femoral stem offset (36.0 ± 7.7 mm versus 40.8 ± 7.3 mm, P = 0.008), increased femoral head offset (0.7 ± 3.4 versus 4.5 ± 3.7, P < 0.001), and the use of Ti-12Mo-6Zr-2Fe alloy stems ( P = 0.041). The presence of ALTR was notably associated with higher chromium (2.0 versus 0.5 μg/L) and cobalt (7.4 versus 0.7 μg/L, P < 0.001). Discussion: This study identified increased femoral head and stem offset and the use of Ti-12Mo-6Zr-2Fe alloy stems as risk factors for clinically relevant ALTR due to head-neck taper corrosion in MoP THA patients. This provides evidenced-based practical information for surgeons in identifying "at-risk" symptomatic MoP THA patients with head-neck taper corrosion for systematic risk stratification.